Effect of the residual atmosphere pressure on collective acceleration of ions in the Luce diode; Vacuum; Vol. 187 - Ryzhkov V. A. Vladislav Andreevich; Remnev (Remnyov) G. E. Gennady Efimovich; Pyatkov I. Igor; Zhuravlev M. V. Mikhail Valerievich (2021, 2021)
Title screen